Contextual Role-Play to Improve ESP Speaking in Islamic Economics Education - Hikmah, Zizi Nur; Yuswandari, Kurnia Devi (Mastery: Master of English Language Journal, 2025)
This study aims to explore the effectiveness of contextual role-play strategies in improving students’ speaking skills in English for Specific Purposes (ESP) classes. The participants were 34 fourth-semester students from the Islamic Economics and Islamic Banking Study Programs at the Institut Agama Islam Sunan Kalijogo Malang. This research employed a descriptive qualitative approach through two learning cycles: the first cycle focused on asking and responding to requests, and the second cycle focused on giving opinions in an Islamic finance context. Data were collected through observation, written reflections, and semi-structured interviews. The results indicated that contextual role-play effectively enhanced students’ confidence, strengthened their mastery of Islamic finance vocabulary, and increased active participation in oral communication. Students responded positively to this method, as they found it relevant, enjoyable, and reflective of real professional situations. These findings are supported by previous studies that highlight the importance of contextualization in ESP-based speaking instruction.